Characteristics and Influencing Factors of Hardness and Thickness of Aeolian Sandy Soil Crust at Sandy Area of Yellow River Floodplain - Li Xinhao; Cao Wenhua; Niu Yong; Lü Qingxia; Yuan Li; Zhao Lei (Shuitu baochi tongbao)
[Objective] The characteristics of the hardness and thickness of a sandy soil crust in Yellow River floodplain and their influencing factors were studied in order to provide scientific references for the protection of soil resources. [Methods] Four different underlying surface treatments, i.e., cultivated land with two crops in a year (T1), cultivated land with one crop in a year (T2), bare land (T3), and spontaneous recovery land (T4), were designed to conduct the experiment. The hardness and thickness of the soil crust, meteorological factors, and vegetation factors were observed and recorded, and the relationships among the hardness and thickness of soil crust and influencing factors were explored by statistical tests and correlation analysis. [Results] The average value of soil crust hardness of T3 was the highest among the four treatments, followed by T4, T1, and T2. Significant correlations between soil crust hardness and soil temperature, vegetation height, vegetation coverage, and near-ground surface wind speed were observed under T1 and T2 (p<0.05). The soil crust thickness of T1 was the highest, followed by T3, T2, T4. There was a significant positive correlation between soil crust thickness and near-surface wind speed for T1 and T2 (p<0.05), and soil crust thickness was significantly correlated with cumulative water replenishment and soil temperature (p<0.05) under T3 and T4. For the treatments located in cultivated land, the contribution of vegetation to crust hardness and thickness was the highest, reaching 37%. For the treatments located in uncultivated land, the contribution of near-ground surface wind speed and cumulative water replenishment to crust thickness and hardness was above 51% and 45%, respectively. [Conclusion] Artificial cultivation was not conducive to the formation of aeolian sandy soil crust and the maintenance of hardness in the Yellow River floodplain. Crust thickness and hardness were significantly affected by vegetation, temperature, and wind speed near the ground surface. Aeolian sandy soil crust thickness, hardness change trend, and surface water content showed the characteristics of synchronous change, while the response of soil crust hardness exhibited some hysteresis. The main driving factors of soil crust hardness and thickness of aeolian sandy soil with cultivation measures were different from those without cultivation measures.